2015
DOI: 10.11622/smedj.2015003
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation of urinary biomarkers to creatinine for clinical practice and research – when and why

Abstract: Acute kidney injury (AKI) and chronic kidney disease (CKD) are major health problems. Urinary biomarkers have both diagnostic and prognostic utility in AKI and CKD. However, how biomarker excretion rates should be reported, especially whether they should be normalised to urinary creatinine concentration (uCr), is controversial. Some studies suggest that normalisation to uCr may be inappropriate at times, as urinary creatinine excretion rate may vary greatly, depending on the situation. Notably, recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 48 publications
1
67
0
1
Order By: Relevance
“…Dichotomized uKIM-1/Cr of high and low levels based on an observed median value of 0.2417 pg/g was used in the analysis. Creatinine indexing may be inappropriate in the setting of AKI [18] due to inconsistent creatinine excretion, but in the setting of chronic disease including the ADPKD population creatinine indexing is more common [19].…”
Section: Predictorsmentioning
confidence: 99%
“…Dichotomized uKIM-1/Cr of high and low levels based on an observed median value of 0.2417 pg/g was used in the analysis. Creatinine indexing may be inappropriate in the setting of AKI [18] due to inconsistent creatinine excretion, but in the setting of chronic disease including the ADPKD population creatinine indexing is more common [19].…”
Section: Predictorsmentioning
confidence: 99%
“…This is in comparison to other biofluids, such as serum, plasma, and cerebrospinal fluids, which are physiologically and homeostatically managed by the body, resulting in much more controlled metabolite concentrations. When urine is sampled, factors such as the collection time and the flow rate can cause fluctuations in the concentrations of urinary metabolites [ 4 , 8 , 9 , 10 ]. It has been reported that the total concentration of urinary metabolites, regarded as urine sample concentration, can vary by more than 15-fold between samples [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation and measurements were carried out according to the manufacturer's protocol and have been described in detail elsewhere (Wang-Sattler et al 2008). Serotonin concentrations were normalized to creatinine levels as earlier described (Tang et al 2015).…”
Section: Laboratory Methodsmentioning
confidence: 99%